Optical coherence tomography for margin definition of basal cell carcinoma before micrographic surgery—recommendations regarding the marking and scanning technique. Issue 1 (23rd October 2017) - De Carvalho, N.; Schuh, S.; Kindermann, N.; Kästle, R.; Holmes, J.; Welzel, J.
Abstract: Background/purpose: Mohs Micrographic Surgery (MMS) is the preferred therapeutic treatment for high‐risk basal cell carcinoma (BCC). Optical Coherence Tomography (OCT) is a non‐invasive imaging technique that enables the diagnosis of BCC. We thought to determine the margins of BCCs with OCT, prior to MMS, to reduce the number of surgical steps. Methods: Different permanent markers were tested on the skin regarding line width, resistance against disinfection and brightness in the OCT image. The visible tumor margins of BCCs were defined by dermoscopy, adding a safety margin of 2 mm and labeled using the selected pen, causing a signal shadow in OCT. Scans of the center and of entire margin were performed. If parts of the BCC were visible outside the margin, another 2 mm were added and the scan was repeated until the tissue outside the labeling looked tumor free. Results: Eight out of ten BCCs were totally excised in a single stage when margin delineation was done by OCT. Macroscopic margins were enlarged after OCT scanning in four patients, saving further stages of MMS. Conclusion: OCT may help to better define the microscopic dimensions of BCCs and therefore reduce the number of stages of MMS.